Replika and the Emotional Artificial Intelligence Company: The ethical and social challenges of company chatbots - Morton Gutiérrez, Jorge Luis (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Tools like language neural networks and machine learning are common today. However, these artificial intelligence tools violate some ethical principles linked to human rights such as privacy and transparency, in addition to the fact that technology is imitating human behavior better and better, which is why it can induce antisocial behavior. Therefore, the work will seek to analyze the social and ethical impact of companion chatbots platforms, especially the case of the Replika platform.